Stress and Burnout Among Gynecologic Oncologists: A Society Of Gynecologic Oncology Evidence-Based Review and Recommendations. Issue 12 (December 2016) - Cass, Ilana; Duska, Linda R.; Blank, Stephanie V.; Cheng, Georgina; duPont, Nefertiti C.; Frederick, Peter J.; Hill, Emily K.; Matthews, Carolyn M.; Pua, Tarah L.; Rath, Kellie S.; Ruskin, Rachel; Thaker, Premal H.; et al.
Abstract : (Abstracted from Gynecol Oncol 2016;143:421–427) Burnout in physicians is a significant problem in all fields of medicine. A 2008 survey of members of the American College of Surgeons (ACS) and a 2014 survey of members of the Society of Gynecologic Oncology (SGO) reported that physician burnout occurs in 32% to 40% of gynecologic oncologists and surgeons This article describes the risk factors responsible for burnout in gynecologic oncologists and other physicians and the consequences of burnout and explores potential solutions.